Yield, chemical composition, and feeding value of winter cereal silages and hays: A 3 year study - S. Azimi; K. Bolsen; A. Laytimi; S.H.M. Esmail; J. Hoover; Q.K. Ye (Kansas Agricultural Experiment Station Research Reports, 1988)
Three trials were conducted to compare silage and hay yields and feeding values of winter cereal foraged harvested in the boot and dough stages of maturity. Included were triticale; common rye; Kanby barley; and Centurk, Arkan, and Bounty 205 wheats. As expected, forage dry matter (DM) yields were higher at the dough stage then boot stage, and silage yields tended to be higher than those for hay. In Trials 2 and 3 (1986-87), barley and rye forage yields were lower than wheat yields. In all three years, wet weather conditions made hay-making difficult. In Trial 1, cattle performance from dough stage wheat (Centurk) and triticale, both silages and hays, was very poor, with daily gains from .9 to 1.2 lb and DM intakes below 2.0% of body weight. Triticale and Centurk wheat forages were high in fiber, and their dough silages had low intakes and digestibilities. Digestion trial results indicated that Arkan and Bounty wheats, Kanby barley, and rye generally had higher feeding values at the boot stage than at the dough stage, and that how well the silage or hay was preserved was a major factor influencing final feeding values.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen& #x27; s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Yield; Feed value; Chemical composition; Cereal silages; Hay